EVALUATION OF ANTIOXIDANT PROPERTIES AT DIFFERENT GERMINATION STAGES OF SEEDS OF NIGELLA SATIVA - DR.DEVENDRA SINGH KUSHWAH, (International Journal of Pharma and Bio Sciences, 2014)
Among the promising medicinal plants, Nigella sativa, also known as Black seeds and Black cumin, has been called the “Blessed Seed” for its miraculous curing ability. Present study has been carried out to evaluate anti-oxidant properties at different germination stages of seeds of Nigella sativa. The level of antioxidant enzymes, SOD and CAT decreased gradually in the samples from first day to fourth day. The activity of SOD and CAT was significantly higher in seed sample as compared to first four days after the start of imbibition. Contrary to CAT and SOD activity, PEROXIDASE activity showed significant increase during germination till sixth day after which there was a decline till 8th day of germination. we can conclude that activities of the antioxidative enzymes CAT and SOD may be involved in preserving the viability of seeds and protecting them from reactive oxygen species formed during storage and seed germination. Peroxidase activity may have a role in the early stages of development of Nigella seedlings. In order to further investigate the role of PEROXIDASE in the early and later stages of seedling development, this isoform of PEROXIDASE has to be analyzed by isolation and kinetic characterization.